OPTIMASI MANAGEMET SUPLY CHAINBAHAN BAKU KEDELAI IMPOR DI MASA PANDEMI COVID-19 MENGGUNAKAN METODE AHP - Nuriyanto; Mas'ud, M. Imron (Journal Knowledge Industrial Engineering (JKIE), 2020)
PT.Joyo Continues is a company engaged in shipping services and distributors of imported soybeans from abroad such as the USA, Brazil and Argentina which will be distributed again to local soybean craftsmen, especially the Pasuruan region and its surroundings, this research was conducted to determine which suppliers are really effective and suitable according to the characteristics of the company, as well as being able to provide the best profit for the company, this research is also intended to help companies determine strategies in facing increasingly competitive market competition. Selection of this supplier uses the AHP (Analytical Hierarchy Process) and SWOT (Strengths Weakeness Opportunity Threats) method. SWOT analysis is a systematic identification of various factors to formulate a company strategy. While AHP is a multicriteria decision-making technique, in which quantitative factors and qualitative factors are combined, so that quality, position, and evaluation can be carried out in the form of variable-variative evaluations (Saaty, 1994). , quality, distribution and consistency as well as company strategy to optimize marketing strategy amidst the global crisis caused by the pandemic, obtained the USA as an alternative to the main supplier.